Families, Crime and Criminal Justice: Charting the Linkages - Benson, Michael L (2000)
Contemporary Perspectives in Family Research is a series of volumes that features scholarly work on the frontiers of interdisciplinary research on families and family life. Volume 2, Families, Crime and Criminal Justice reflects this pioneering orientation by bringing together new empirical research that examines the various ways that families intersect with and are affected by crime and the criminal justice system. The interdisciplinary nature of the volume is reflected in the diversity of disciplines represented, including developmental psychopathology, criminology, sociology, family studies, psychology, social work and demography. The inclusion of qualitative studies based upon observational techniques and in-depth, long interviews as well as quantitative work using demographic and survey approaches demonstrates the wide methodological range employed by the authors. The topics examined include the involvement of children in crime, the patterns and impact of violence in the home, the impact of criminal involvement on parenting strategies and youth development, the experience of families of victims and perpetrators, and responses of the criminal justice system to the needs of families